Effectiveness of beta-blockers in the treatment of idiopathic premature ventricular contractions in children - K. B. Alekseeva; T. K. Kruchina; M. Sh. Malyarova; G. A. Novik (Российский кардиологический журнал)
Aim. To evaluate the effectiveness of beta-blockers (BB) in the treatment of idiopathic premature ventricular contractions (PVCs) in children.Material and methods. BBs were prescribed to 27 children with idiopathic PVCs. In 3 (11,1%) patients, side effects (hypotension, bronchial obstruction) was revealed at the beginning of therapy. A total of 24 children were included in the further study (15 boys (62,5%), 9 girls (37,5%). The mean age was 8,3±5,4 years. Data from anamnesis, electrocardiography (ECG), 24-hour ECG monitoring, and echocardiography were analyzed.Results. The 24-hour PVC rate was 33,2±17,7 thousand/day or 26,6±13,2%. In 14 (58,3%) children, we recorded paired PVCs, in 3 (12,5%) — multiform, in 10 (41,7%) — runs of non-sustained VT. There were complaints in 7 (29,2%) children. The follow-up period lasted 369,8±119,1 days. Propranolol was received by 17 (70,8%) patients, metoprolol — by 7 (29,2%). The therapy was effective in 11 (45,8%) patients, while ineffective in 13 (54,2%), among which 5 (20,8%) had an increase in the number of PVCs. The effectiveness of BBs was higher in children under the age of 1 year (p=0,043). Propranolol showed greater efficacy than metoprolol (p=0,047). Less efficiency was observed in female patients and those with pathological heart rate turbulence parameters (p=0,04).Conclusion. The effectiveness of BBs in children with idiopathic PVCs is 45,8%, higher in children aged <1 year and declines with age, decreasing in adolescents to 25%. The use of BBs is limited by non-cardiac side effects in 11,1% of children. Propranolol is more effective than metoprolol.